BIOLOGICAL NOTES ON KING MACKEREL, SCOMBEROMORUS CAVALLA (CUVIER), FROM NORTHEASTERN BRAZIL - Nomura, Hitoshi; Rodrigues, Maria Sílvia de Sousa (Arquivos de Ciências do Mar, 2018)
The main species of fish of_ ~ommer~ial importance in northeastern Brazll 1s the kmg mackerel Scomberomorus cavalla (Cuvier). It is fmind in the western Atlantic, from Maine to Brazil (Robins, 1958) . Some biological notes on the king mackerel are given in this paper. concerning its ccmdition factor, age and growth in terms oi fork length and weight.